2021
DOI: 10.1055/s-0040-1716898
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Subset: Idiopathic Intracranial Hypertension Presenting as Spontaneous CSF Leak of the Anterior Skull Base

Abstract: Background Spontaneous cerebrospinal fluid (CSF) leaks represent a unique clinical presentation of idiopathic intracranial hypertension (IIH), lacking classical features of IIH, including severe headaches, papilledema, and markedly elevated opening pressures. Methods Following a single-institution retrospective review of patients undergoing spontaneous CSF leak repair, we performed a literature review of spontaneous CSF leak in patients previously undiagnosed with IIH, querying PubMed. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Leading Topic Editor: Olga P. Fermo, MD, Department of Neurology, Mayo Clinic, Jacksonville, Florida, United States unknown causes [1,2]. Primary spontaneous CSF leaks represent a unique subset of this condition, characterised by specific features including its target demographic and a high recurrence rate, of 2.9-46% after repair, compared to other types of CSF leak [3,4].…”
Section: E a D I N G T O P I Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Leading Topic Editor: Olga P. Fermo, MD, Department of Neurology, Mayo Clinic, Jacksonville, Florida, United States unknown causes [1,2]. Primary spontaneous CSF leaks represent a unique subset of this condition, characterised by specific features including its target demographic and a high recurrence rate, of 2.9-46% after repair, compared to other types of CSF leak [3,4].…”
Section: E a D I N G T O P I Cmentioning
confidence: 99%
“…Although not all patients with SCSFR have idiopathic intracranial hypertension (IIH), the connection between them was first proposed in 1994 by Clark et al, who identified female gender and obesity as significant risk factors due to their potential to increase intraabdominal pressure, thereby impairing venous return and elevating intracranial pressure (ICP) [6]. Subsequent research has suggested a link between chronic elevated ICP and secondary skull base bony erosion leading to leakage [1,3,7]. Recognising and understanding this relationship is crucial for improving treatment outcomes.…”
Section: E a D I N G T O P I Cmentioning
confidence: 99%
“…Chronic congestion of the lymphatic CSF as it travels through the sheaths of the cranial nerves, around the olfactory bulb, is thought to contribute to erosion of the cribriform plate [57 & ]. It is difficult to make a preoperative diagnosis of IIH in patients with spontaneous CSF leak, as 14% of patients have papilledema preoperatively and CSF pressure is frequently below the cut-off set out in the diagnostic criteria for IIH [58]. Postoperatively, not all patients with spontaneous CSF leak will develop papilledema or fulfil diagnostic criteria for IIH [53 & ].…”
Section: Spontaneous Skull Base Cerebrospinal Fluid Leakmentioning
confidence: 99%
“…It is difficult to make a preoperative diagnosis of IIH in patients with spontaneous CSF leak, as ∼14% of patients have papilledema preoperatively and CSF pressure is frequently below the cut-off set out in the diagnostic criteria for IIH [ 58 ]. Postoperatively, not all patients with spontaneous CSF leak will develop papilledema or fulfil diagnostic criteria for IIH [ 53 ▪ ].…”
Section: Spontaneous Skull Base Cerebrospinal Fluid Leakmentioning
confidence: 99%
See 1 more Smart Citation